Prevalence and abundance of plant-parasitic nematodes associated with corn (Zea mays L.) in Anuradhapura, Sri Lanka - Thiruchchelvan, N.; Casonato, S.; Mikunthan, G.; Condron, L.; Moukarzel, R.; Kularathna, M. (National Science Foundation of Sri Lanka, 2024)
The prevalence and abundance of plant-parasitic nematodes (PPNs) associated with corn (Zea mays; Poaceae) in the Anuradhapura district of Sri Lanka are poorly understood. This study investigated the occurrence and population densities of major PPN genera associated with corn. Over 92% of the corn fields were positive for PPNs in all the sampled fields. Major PPN genera identified were Pratylenchus spp. (71.4%), Helicotylenchus spp. (28.6%), Meloidogyne spp. (21.4%), Criconemella spp. (21.4%), and Hoplolaimus spp. (35.7%). The mean population density of Pratylenchus spp. was 2020 nematodes kg-1 of soil, in the Anuradhapura corn fields. During the cropping season from November (2021) to February (2022), all PPN genera except Meloidogyne spp. were observed. Pratylenchus spp. were detected at levels below 1000 nematodes kg-1 of soil at the seedling stage, except in Kelenikawewa where the initial population was 1865 nematodes kg-1. At the time of harvest, Pratylenchus spp. increased by 2 to 10 folds. These findings suggest a potential impact of Pratylenchus spp. on corn yield in Anuradhapura, highlighting the need for further research to assess damage levels and the overall effect of PPNs on corn production in Sri Lanka.
Keywords: Anuradhapura; Nematode diversity; Plant-parasitic nematodes; Pratylenchus; Sri Lanka; Zea mays (maize)